An orthodontic-surgical approach to Class II subdivision malocclusion treatment (Journal of Applied Oral Science, 2009)
Despite the different orthodontic approaches to Class II subdivision malocclusions one has also to consider the skeletal components before undertaking any treatment protocol. Significant involvement of the skeletal structures may require a combined surgical orthodontic treatment, which has remained stable for more than four years, as illustrated in this case report.